Chemical components from dark of garcinia mangostana l. / Nurulhuda Ruseli - Ruseli, Nurulhuda (Faculty of Applied Sciences, 2016)
Experiment was conducted on bark of Garcinia mangostana which belong to the family Clusiaceae found throughout in the tropical region of the entire world. This genus of species contain varies of medicinal benefit such as anti-cancer, antimicrobial and anti-imflammatory. Several objectives have been set up for this experiment which is first to extract and isolate the chemical constituents from bark of Garcinia mangostana L., meanwhile for the second one is to identify and elucidate the structure of the compounds by using spectroscopic methods. Experiment on the isolation from bark of Garcinia mangostana through a series of column chromatography have resulted on the isolation of three prenylated xanthones, mangostin, mangostin and 9-hydroxycalabaxanthone. All of these structures were established by spectroscopic analysis which included ID NMR, MS techniques and comparing with previous data.